2011
DOI: 10.1074/jbc.m111.234674
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-Mediated Cell Death of Cultured Hippocampal Neurons Reveals Extensive Tau Fragmentation without Increased Full-length Tau Phosphorylation

Abstract: A variety of genetic and biochemical evidence suggests that amyloid ␤ (A␤) oligomers promote downstream errors in Tau action, in turn inducing neuronal dysfunction and cell death in Alzheimer and related dementias. To better understand molecular mechanisms involved in A␤-mediated neuronal cell death, we have treated primary rat hippocampal cultures with A␤ oligomers and examined the resulting cellular changes occurring before and during the induction of cell death with a focus on altered Tau biochemistry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
74
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 60 publications
8
74
0
Order By: Relevance
“…Treating cell cultures with multiple forms of Aβ, including soluble Aβ1-42 [40], Aβ oligomer [41], and Aβ fibril [42] induces tau hyperphosphorylation. Aβ-induced tau hyperphosphorylation consequently caused microtubule disassembly [41,43], reduction of total soluble tau and an increase in tau fragments [44], missorting of tau into dendritic areas [41], activation of the nuclear transcription factor of activated T cells' apoptotic pathways [45,46], and cell toxicity [41,44]. 2xTg (tau and APP mutant) or 3xTg (tau, APP and PS mutant) mice exhibit enhanced neurofibrillary tangle formation [47][48][49][50], which was attributed to activation of glycogen synthase kinase (GSK)-3β and Cdk5 [49,51], and inhibited proteasome activity [50].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%
“…Treating cell cultures with multiple forms of Aβ, including soluble Aβ1-42 [40], Aβ oligomer [41], and Aβ fibril [42] induces tau hyperphosphorylation. Aβ-induced tau hyperphosphorylation consequently caused microtubule disassembly [41,43], reduction of total soluble tau and an increase in tau fragments [44], missorting of tau into dendritic areas [41], activation of the nuclear transcription factor of activated T cells' apoptotic pathways [45,46], and cell toxicity [41,44]. 2xTg (tau and APP mutant) or 3xTg (tau, APP and PS mutant) mice exhibit enhanced neurofibrillary tangle formation [47][48][49][50], which was attributed to activation of glycogen synthase kinase (GSK)-3β and Cdk5 [49,51], and inhibited proteasome activity [50].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%
“…Taken together, the data suggest that there is an intrinsic relationship between Aβ and Tau dysfunction. It has been shown that the deposition of Aβ induced the activation of calpain-1 and caspase-3 proteases [2,5,8] . These proteases cleave Tau proteins at specific sites, generating toxic Tau fragments or enhancing the aggregation properties of Tau protein [2,5,9] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the deposition of Aβ induced the activation of calpain-1 and caspase-3 proteases [2,5,8] . These proteases cleave Tau proteins at specific sites, generating toxic Tau fragments or enhancing the aggregation properties of Tau protein [2,5,9] . The activation of these proteases, Tau cleavage, and the extent of neurodegeneration are both time-and dose-dependent [2,5,9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations